Addressing the Thinking Mind: A Constructivist Approach to Informational Stories for Children - Yanilla Aquino, Lalaine (Journal of English Studies and Comparative Literature; Vol 9 No 1 (2006), 2007)
Excerpt Constructivism is an approach to teaching and learning, but it can also be an approach to children’s literature—particularly the type of children’s stories that are also meant to provide particular information or teach particular concepts. For lack of a better term and for the purpose of this paper, such stories are hereupon termed informational stories . To show how the constructivist approach can be used to evaluate such stories, four informational stories published by Adarna House will be analyzed: Heidi Eusebio Abad’s Polliwog’s Wiggle , Carla Pacis’s Hipon and Biya , Robert Magnuson’s Mister Beetle’s Many Rooms , and Christine Bellen’s Filemon Mamon .